Mengidentifikasi Faktor-Faktor yang Mempengaruhi Ketidakteradaan Manual Prosedur pada UKM - Untajan, Paulus Perey; Kopong, Anthoneta (Jurnal Manajemen dan Teknologi, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in Indonesia’s economy, but many face challenges in managing operations efficiently. One of the main issues is the lack of well-documented procedures. This study aims to identify the factors that hinder the implementation of procedure manuals in SMEs and provide recommendations for improving managerial and operational systems. Factors such as limited human resources, lack of understanding of the importance of documentation, and technological constraints were found to be the biggest obstacles. Additionally, managerial policies and corporate culture also affect the implementation of necessary procedures. Using a quantitative approach through surveys distributed to 80 SMEs in Jakarta, the study analyzes data using descriptive statistics and T-tests to identify differences between groups. The results show that costs and time constraints are the main factors hindering the implementation of procedure manuals, while business size and knowledge of procedures also play significant roles. The findings aim to provide practical recommendations for SMEs to enhance their operational efficiency and quality by implementing more structured procedures.